2022
DOI: 10.1155/2022/4811191
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Artistic Creation Style Extraction Model Based on Color Feature Data

Abstract: In order to improve the style extraction and extraction ability of works of art, a color extraction method based on color features is proposed. The color feature extraction method is used to extract the style of visual works of art. The color feature region of works of art is segmented combined with a sparse scattered point reorganization method. Texture tracking and matching method is used for information fusion of works of art, combined with corner detection, three-dimensional edge contour feature detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The visual expression ability of the artwork is enhanced by merging the information of the artwork through the texture matching method. The results show that the fuzzy clustering algorithm improves the aesthetic feature extraction and recognition of artworks, the accuracy of the algorithm is high, and the extraction ability of artworks is good [5]. Wang, R. et al used the method of direct evaluation of single-item measurement to study and analyze the influence of urban green space characteristics on aesthetic preferences, and the results showed that the more flowers and trees present in the image, the more people's preferences will increase.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The visual expression ability of the artwork is enhanced by merging the information of the artwork through the texture matching method. The results show that the fuzzy clustering algorithm improves the aesthetic feature extraction and recognition of artworks, the accuracy of the algorithm is high, and the extraction ability of artworks is good [5]. Wang, R. et al used the method of direct evaluation of single-item measurement to study and analyze the influence of urban green space characteristics on aesthetic preferences, and the results showed that the more flowers and trees present in the image, the more people's preferences will increase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mingjie Shen. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%
“…Artistic design is the process of activity that conveys a plan, planning, and vision through a visual form [4]. Art design has also been explained as the pre-development of a work program and plan by the purpose and requirements of the task, drawing the patterns and diagrams needed to solve this problem [5][6]. With the development and progress of society, art design encompasses an increasingly wide range, such as product design, environmental design, graphic design, clothing design, packaging design, and so on [7][8].…”
Section: Background Of the Studymentioning
confidence: 99%
“…Conventional coating defect detection is the inspection and judging of coating quality and the recording of the type and level of defects the staff produces within a specific time after the painting is completed. This method relies on domain experts or field technicians to identify the underlying visual features of defects, such as color [9][10][11][12], shape [13][14][15][16], and texture [17][18][19][20] through professional knowledge and practical experience, which not only increases the work intensity and work pressure of personnel but also greatly increases time cost, making it difficult to ensure the accuracy of coating defect identification [21] and the efficiency of coating operations [22]. With proposals based in ship manufacturing theory and the continuous popularization of artificial intelligence in the ship painting industry, people have begun to gradually apply intelligent technology to the understanding of ship painting defects, but there are fewer reports on the application of image-based ship coating defects recognition.…”
Section: Introductionmentioning
confidence: 99%